2007
DOI: 10.1097/meg.0b013e3281bcb784
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treatment of oesophageal variceal bleeding in patients with cirrhosis in France: results of a French survey

Abstract: Management of variceal bleeding is very costly compared with other digestive diseases. In particular, additional treatment needed because of failure to control bleeding or early rebleeding makes the management expensive. The severity of the underlying liver disease has a great impact on treatment outcome, leading to higher treatment costs for class C patients than less affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…The cost of treating an oesophageal varices bleed is assumed to be £10,000. This has been estimated from a weighted average of costs presented by Thabut et al, 161 which was €11,982; these costs are similar to figures reported in Wechowski et al 162 9. An endoscopy once every 3 years to be provided for those without varices and every 2 years for those patients with small or moderate varices.…”
Section: Incorporating Oesophageal Varices Bleedingsupporting
confidence: 71%
“…The cost of treating an oesophageal varices bleed is assumed to be £10,000. This has been estimated from a weighted average of costs presented by Thabut et al, 161 which was €11,982; these costs are similar to figures reported in Wechowski et al 162 9. An endoscopy once every 3 years to be provided for those without varices and every 2 years for those patients with small or moderate varices.…”
Section: Incorporating Oesophageal Varices Bleedingsupporting
confidence: 71%
“…There was a significant increase in both the length of stay and cost of care over the study period. This finding is likely due to an aging population and the multiple comorbidities experienced by older patients (23).…”
Section: Discussionmentioning
confidence: 98%
“…Врло честа неуспешна контрола крварења као и рано поновно крварење чине ову терапију изузетно скупом у поређењу са трошковима лечења других болести дигестивног система (36). Једна фармакоекономска студија у Француској показала је да просечни трошкови болничког лечења пацијената са акутним вариксним крварењем, који су праћени 46 дана а захтевали су само иницијалну терапију заустављања крварења, износе 9.906 евра.…”
Section: фармакоекономске анализе употребе соматостатина и његових анunclassified
“…Једна фармакоекономска студија у Француској показала је да просечни трошкови болничког лечења пацијената са акутним вариксним крварењем, који су праћени 46 дана а захтевали су само иницијалну терапију заустављања крварења, износе 9.906 евра. Просечни трошкови лечења пацијената код којих иницијални третман није дао успеха износе 23.113 евра и 29.406 евра за пацијенте којима су потребне једна или две додатне процедуре за успостављање контроле крварења (36).…”
Section: фармакоекономске анализе употребе соматостатина и његових анunclassified